Witchcraft in Post-colonial Africa : Beliefs, techniques and containment strategies - Mavhungu, Khaukanani (Book collections on Project MUSE., 2012)
This is a comparative ethnographic study of witchcraft and associated violence between the kingdoms of Kom and Venda in Cameroon and South Africa respectively. The book shows why despite its prevalence in both societies, witchcraft does not lead to open violence in Kom, while such large-scale violence is commonplace in Venda. It reveals that this difference can be explained by factors such as the variations in local ideas on witches, differences in the role of traditional authorities, and various state interventions on witchcraft matters. The book demonstrates, through a rich collection of detailed cases, that contrary to anthropological theory that views witchcraft as a mechanism for the expression and resolution of social tensions and conflicts, witchcraft may at times become a disturbance of amicable social relations. Witchcraft accusations may occur in a context where strained social relations have not preceded them. The knowledge and experience that people have about witchcraft is sufficient to trigger an accusation and a violent reaction. Different forms of witchcraft account for variations in witchcraft attributions and accusations. This comparison provides a valuable contribution to ongoing witchcraft policy discourse amid widespread citizen anxiety over witchcraft, and the increasing call on the post-colonial state to intervene and protect its citizens against occult aggression.